Flame-retardant polyolefin resin composition

JP7642988B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2020120684
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-27
Filing Date
2020-07-14
Publication Date
2025-03-11
Estimated Expiration
2040-07-14

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、難燃性と引張特性とを両立し、成形加工性に優れた難燃性ポリオレフィン系樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007642988000001
    Figure 0007642988000001
  • Figure 0007642988000002
    Figure 0007642988000002
Patent Text Reader

Abstract

To provide a flame-retardant polyolefin-based resin composition which achieves both flame retardancy and tensile characteristics, and is excellent in moldability.SOLUTION: There are provided a flame-retardant polyolefin-based resin composition that contains the following components (A) to (D), and contains 5-70 pts.mass of the component (B) with respect to 100 pts.mass of the component (A); and a molding of the same. An MFR (190°C and load of 21.2 N) of the flame-retardant polyolefin-based resin composition is preferably 1.0-5.0 g / 10 min. Component (A): ethylenic resin component. Component (B): scaly magnesium hydroxide. Component (C): silicone. Component (D): softening agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a flame-retardant polyolefin resin composition. [Background technology]

[0002] Polyvinyl chloride resin compositions have excellent electrical insulation properties and self-extinguishing flame retardant properties, and are therefore widely used in wire coatings, tubes, tapes, building materials, automobile parts, home appliance parts, etc. However, since polyvinyl chloride resin compositions contain chlorine, they generate hydrogen chloride gas, which is a corrosive gas, when burned, and there is a risk of generating toxic gases such as dioxins depending on the combustion conditions. For this reason, as part of measures against environmental issues, halogen-free materials (hereinafter, not containing halogen may be referred to as "non-halogen") that are unlikely to generate these toxic gases when burned have come to be used.

[0003] Non-halogenated materials include polyolefin resins such as polypropylene and polyethylene, and styrene resins. However, polyolefin resins are not flame retardant, so they need to be made flame retardant depending on the application. As a countermeasure, a method of adding halogenated flame retardants has been used for a long time. However, since halogenated flame retardants can also generate toxic gases when burned, a method of adding metal hydroxides such as magnesium hydroxide and aluminum hydroxide as non-halogenated flame retardants has been adopted recently.

[0004] For example, an oil-resistant flame-retardant resin composition is known that uses a polyolefin resin such as polyethylene, a metal hydrate such as magnesium hydroxide or aluminum hydroxide as a flame retardant, and silicon powder or zinc hydroxystannate as a flame retardant assistant, thereby keeping the amount of metal hydrate added low and preventing a decrease in mechanical properties (Patent Document 1). Also, a technology is known that improves the oxygen index by combining a polyolefin resin with magnesium hydroxide, an organic silicone compound, etc. (Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2002-284935 A [Patent Document 2] JP 2006-143896 A [Patent Document 3] JP 2011-256294 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, the polyolefin-based flame-retardant resin compositions containing magnesium hydroxide, aluminum hydroxide, or the like, which have been conventionally used in Patent Documents 1 to 3, still have room for improvement in terms of molding processability and tensile properties due to the influence of the flame retardant filled therein in order to obtain the required flame retardant performance.

[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a flame-retardant polyolefin resin composition which has both flame retardancy and tensile properties and is excellent in moldability. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to solve the above problems, and have found that a polyolefin resin composition containing an ethylene resin component, a specific magnesium hydroxide, and a silicone in a specific mixing ratio can achieve a flame-retardant polyolefin resin composition that is both flame retardant and has good tensile properties and excellent moldability. The present invention has been achieved based on these findings, and is summarized as follows.

[0009] [1] A flame-retardant polyolefin-based resin composition comprising the following components (A) to (D), wherein the flame-retardant polyolefin-based resin composition contains 5 to 70 parts by mass of component (B) per 100 parts by mass of component (A): Component (A): Ethylene-based resin component Ingredient (B): Scaly magnesium hydroxide Component (C): Silicone Component (D): Softener

[0010] [2] The flame-retardant polyolefin resin composition according to [1], wherein the flame-retardant polyolefin resin composition has an MFR (190° C., 21.2 N load) of 1.0 to 5.0 g / 10 min.

[0011] [3] The flame-retardant polyolefin resin composition according to [1] or [2], comprising 7 to 65 parts by mass of the component (B) per 100 parts by mass of the component (A).

[0012] [4] A molded article using the flame-retardant polyolefin resin composition according to any one of [1] to [3]. Effect of the Invention

[0013] According to the present invention, it is possible to provide a flame-retardant polyolefin resin composition which has both flame retardancy and tensile properties and is excellent in moldability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below, but the present invention is not limited to the following description, and can be modified as desired without departing from the gist of the present invention. In this specification, when a numerical value or physical property value is enclosed before and after "~", the value before and after the "~" is included.

[0015] [Flame-retardant polyolefin resin composition] The flame-retardant polyolefin resin composition of the present invention is a mixture containing the following components (A) to (D) (hereinafter sometimes referred to as "the mixture of the present invention"). Component (A): Ethylene-based resin component Ingredient (B): Scaly magnesium hydroxide Component (C): Silicone Component (D): Softener

[0016] The MFR (190°C, 21.2N load) of the flame-retardant polyolefin resin composition of the present invention is preferably 1.0 to 5.0g / 10min, more preferably 2.0 to 4.0g / 10min, from the viewpoint of moldability. Here, the MFR of the flame-retardant polyolefin resin composition is the melt flow rate measured at a temperature of 190°C and a load of 21.2N in accordance with JIS K7210-1.

[0017] The oxygen index of the flame-retardant polyolefin resin composition of the present invention, as measured in accordance with JIS K7201, is preferably 22-28, more preferably 24-28, from the viewpoint of flame retardancy.

[0018] From the viewpoint of molding processability, the extrusion load of the flame-retardant polyolefin resin composition of the present invention is preferably 5 to 15 MPa, and more preferably 10 to 15 MPa, when an extruded tape having a thickness of 1 mm and a width of 4 cm is produced using an extruder with a diameter of 20 mm under conditions of a temperature condition of 180°C and a screw rotation speed of 60 rpm.

[0019] [Component (A)] Component (A) is an ethylene-based resin component. Examples of ethylene-based resins include various polyethylenes, such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE). Here, polyethylene means a polymer or copolymer containing ethylene as a main component as a raw material monomer, and preferably containing 50% by mass or more of ethylene units. In addition, the polyethylene may be one obtained by modifying these resins with unsaturated carboxylic acids such as maleic anhydride, maleic acid, and acrylic acid, or derivatives thereof, unsaturated silane compounds, or the like. Furthermore, it may have a partially crosslinked structure. Examples of ethylene-based resins other than polyethylene include ethylene-vinyl acetate copolymers and ethylene-α-olefin copolymers. These may be used alone or in combination of two or more.

[0020] Examples of commercially available polyethylene include "Novatec LL" (registered trademark) manufactured by Japan Polyethylene Corporation and "Modic" (registered trademark) manufactured by Mitsubishi Chemical Corporation, and any suitable polyethylene can be selected and used.

[0021] The ethylene-vinyl acetate copolymer means a copolymer having at least a unit derived from ethylene and a unit derived from vinyl acetate. In the present invention, even if ethylene and vinyl acetate are not used as raw materials, the copolymer having the same chemical structure after polymerization is included in the ethylene-vinyl acetate copolymer of the present invention.

[0022] Examples of commercially available ethylene-vinyl acetate copolymers include "Novatec EVA" (registered trademark) manufactured by Japan Polyethylene Corporation, "Evaflex" (registered trademark) manufactured by Mitsui DuPont Polychemicals, and "Revaprene" (registered trademark) manufactured by LANXESS AG. Any suitable product can be selected and used.

[0023] The ethylene-α-olefin copolymer is a copolymer of ethylene and an α-olefin, and the α-olefin is usually an α-olefin having 3 to 20 carbon atoms that does not contain a cyclic molecule, such as propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-tetradecene, or 1-octadecene, each of which can be used alone or in a mixture of two or more. The ethylene-α-olefin copolymer may also be one that uses a vinyl ester (vinyl acetate, etc.), an unsaturated carboxylic acid or its ester (acrylic acid, methacrylic acid, methyl acrylate, methyl methacrylate, ethyl acrylate, etc.) as a copolymerization component.

[0024] Commercially available ethylene-α-olefin copolymers include, for example, "Engage" (registered trademark) manufactured by The Dow Chemical Company and "Kernel" (registered trademark) manufactured by Japan Polyethylene Corporation, and can be appropriately selected and used.

[0025] Furthermore, the MFR of component (A) is preferably 1 to 35 g / 10 min, and more preferably 5 to 30 g / 10 min. If the MFR of component (A) is not less than the lower limit, the moldability is good, and if it is not more than the upper limit, the appearance is good. Here, the MFR of component (A) is the melt flow rate measured at a temperature of 190° C. and a load of 21.2 N in accordance with JIS K7210-1.

[0026] As the ethylene resin component of component (A), only one of the above-mentioned various ethylene resins may be used, or two or more of them having different copolymer component compositions or physical properties may be mixed and used. For example, it is preferable to use 30-40% by mass of linear low-density polyethylene, 50-60% by mass of ethylene-α-olefin copolymer, and 5-15% by mass of ethylene-vinyl acetate copolymer as the ethylene-based resin component of component (A) in a total amount of 100% by mass, since this balances moldability and tensile properties. When two or more kinds of components (A) are mixed and used in this way, the same effect can be obtained even if the MFR of each ethylene-based resin component is outside the above-mentioned preferred range, so long as the MFR of the mixture is within the above-mentioned preferred range.

[0027] [Component (B)] In the present invention, flaky magnesium hydroxide is used as component (B) in order to obtain flame retardancy as a flame-retardant polyolefin resin composition.

[0028] Conventionally, magnesium hydroxide generally used is in a particulate form, whereas scaly magnesium hydroxide can be distinguished by its shape. The scaly magnesium hydroxide used in the present invention is in a thin plate form (flake form) like scales, and its planar form (plate surface form) is not particularly limited, such as circular, elliptical, rectangular, or amorphous. From the viewpoint of achieving both flame retardancy and tensile properties of the resulting resin composition, the average diameter of the scaly magnesium hydroxide is preferably 2 to 8 μm, more preferably 3 to 7 μm, and even more preferably 4 to 6 μm. From the same viewpoint, the average thickness of the scaly magnesium hydroxide is preferably 40 to 80 nm, more preferably 45 to 75 nm, and even more preferably 50 to 70 nm. From the same viewpoint, the aspect ratio (average diameter / average thickness) of the scaly magnesium hydroxide is preferably 25 to 200, more preferably 40 to 150, and even more preferably 50 to 100.

[0029] Here, the diameter of the flaky magnesium hydroxide corresponds to the diameter measured by SEM observation if the flaky magnesium hydroxide has a circular planar shape. If the flaky magnesium hydroxide has a non-circular shape, the diameter corresponds to the largest gap between the plates when the plate surface of the flaky magnesium hydroxide is sandwiched between two parallel plates. The average diameter is usually calculated as the average value of the diameters of 100 flaky magnesium hydroxides measured by such SEM observation. Similarly, the average thickness of the flaky magnesium hydroxide is calculated as the average value of the thicknesses of 100 flaky magnesium hydroxide particles measured by SEM observation. The aspect ratio is determined by the ratio of these two. However, the average diameter, average thickness, and aspect ratio of commercially available products may be determined based on catalog values. In the present invention, the average diameter, average thickness and aspect ratio of flaky magnesium hydroxide refer to the average diameter, average thickness and aspect ratio of the flaky magnesium hydroxide used as a raw material before being mixed with component (A) and the like.

[0030] The scaly magnesium hydroxide of component (B) may be used alone or in combination of two or more different shapes and sizes.

[0031] An example of commercially available flaky magnesium hydroxide is "Kisuma 10A" (registered trademark) manufactured by Kyowa Chemical Industry Co., Ltd.

[0032] In the flame-retardant polyolefin resin composition of the present invention, the content of the flaky magnesium hydroxide of component (B) is 5 to 70 parts by mass relative to 100 parts by mass of the total of component (A). The flame-retardant polyolefin resin composition of the present invention contains flaky magnesium hydroxide as a flame retardant in the above range, and thus the flame-retardant polyolefin resin composition has both flame retardancy and tensile properties and is excellent in moldability. The flaky magnesium hydroxide of component (B) is preferably used in an amount of 7 parts by mass or more, more preferably 9 parts by mass or more, and even more preferably 15 parts by mass or more, relative to 100 parts by mass of the total of component (A). On the other hand, the flaky magnesium hydroxide of component (B) is preferably used in an amount of 65 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 50 parts by mass or less, relative to 100 parts by mass of the total of component (A).

[0033] [Component (C)] The mixture of the present invention contains the following component (C) from the viewpoint of improving moldability. The silicone of component (C) contributes not only to improving moldability but also to improving flame retardancy. Component (C): Silicone

[0034] Examples of silicones of component (C) include silicone oils. The silicone oils are preferably those having a kinetic viscosity of 50 to 30,000 cSt at 25° C. Here, the kinetic viscosity of silicone oils at 25° C. can be measured according to JIS Z8803.

[0035] By making the kinetic viscosity of silicone oil at 25°C within the above range, the effect of improving the releasability during molding can be obtained, and at the same time, the bleeding of silicone oil to the surface of molded body can be suppressed, and the appearance can be kept good.In order to make these effects better, the kinetic viscosity of silicone oil at 25°C is more preferably 100cSt or more, more preferably 200cSt or more, while more preferably 25,000cSt or less, more preferably 20,000cSt or less, and particularly preferably 15,000cSt or less.

[0036] As the silicone oil, a linear silicone represented by the following formula (1) can be preferably used.

[0037] [ka]

[0038] In the above formula (1), R represents an organic functional group not containing a functional group involved in a hydrosilylation addition reaction, such as an alkenyl group and / or a SiH group, or a hydroxyl group, and multiple R may be the same or different. x represents an integer of 10 to 30,000. R preferably represents each independently a monovalent hydrocarbon group or a hydroxyl group, more preferably an alkyl group or an aryl group, and further preferably a methyl group, an ethyl group, or a phenyl group.

[0039] The linear silicone represented by the above formula (1) is a polydiorganosiloxane having both ends blocked with triorganosilyl groups, and is preferably a polydialkylsiloxane, a polydiarylsiloxane, a polyalkylarylsiloxane, or a copolymer thereof, more preferably a polydimethylsiloxane or a polymethylphenylsiloxane, and particularly preferably a polydimethylsiloxane in which all R are methyl groups.

[0040] Commercially available polydimethylsiloxanes include SH200 (manufactured by Dow Corning Toray Co., Ltd.), KF-96, KF-96H, KF-965, KF-968 (manufactured by Shin-Etsu Silicones Co., Ltd.), TSF451 (manufactured by Momentive Performance Materials Japan Co., Ltd.), AK, AKF, AKC (manufactured by Wacker Asahi Kasei Silicones Co., Ltd.), etc. Commercially available polymethylphenylsiloxanes include SH510, SH550, SH710 (manufactured by Dow Corning Toray Co., Ltd.), KF-50, KF-53, KF-54 (manufactured by Shin-Etsu Silicones Co., Ltd.), TSF431, TSF433, TSF4300 (Momentive Performance Materials), AR (Wacker Asahi Kasei Silicones), etc. Furthermore, as an organic modified siloxane in which functionality has been enhanced by introducing an organic group onto the silicone backbone, Tegomer V-Si4042 (manufactured by Evonik) and the like are commercially available products.

[0041] Only one type of silicone oil may be used, or two or more types having different kinetic viscosities or different R in the above formula (1) may be used in combination.

[0042] In the flame-retardant polyolefin resin composition of the present invention, the content of silicone in component (C) is preferably 0.1 to 8 parts by mass, more preferably 0.5 to 6 parts by mass, even more preferably 1 to 5 parts by mass, and particularly preferably 2 to 5 parts by mass, per 100 parts by mass of the total of component (A).

[0043] By containing the silicone of component (C) in the above range in the flame-retardant polyolefin resin composition of the present invention, the effects of improving moldability and oxygen index provided by component (C) can be fully obtained while the blending effects of the other components are fully obtained. Furthermore, as will be shown in the examples described later, the use of the silicone of component (C), particularly in combination with the flaky magnesium hydroxide of component (B), can provide an effect of improving the oxygen index, and in order to obtain the synergistic effect of such a combination, it is preferable to use the silicone of component (C) in an amount of 5 to 20 parts by mass, and particularly 5 to 10 parts by mass, per 100 parts by mass of the flaky magnesium hydroxide of component (B).

[0044] [Component (D)] The mixture of the present invention contains the following component (D) from the viewpoint of improving moldability and oil resistance. Component (D): Softener

[0045] As the softener of component (D), a hydrocarbon-based rubber softener is preferably used from the viewpoint of compatibility with resin. Examples of commercially available hydrocarbon-based rubber softeners used as the softener of component (D) include mineral oil-based softeners and synthetic resin-based softeners, but mineral oil-based softeners are preferred from the viewpoint of affinity with other components. Mineral oil-based softeners are generally mixtures of aromatic hydrocarbons, naphthenic hydrocarbons, and paraffinic hydrocarbons, and those in which 50% or more of the total carbon atoms are paraffinic hydrocarbons are called paraffinic oils, those in which 30 to 45% of the total carbon atoms are naphthenic hydrocarbons, and those in which 35% or more of the total carbon atoms are aromatic hydrocarbons are called aromatic oils. Among these, in the present invention, a paraffinic rubber softener that is paraffinic oil is used. The softening agents such as paraffin-based rubber softening agents may be used alone or in any combination and ratio of two or more kinds.

[0046] The kinetic viscosity of the paraffinic rubber softener of component (D) at 40° C. is not particularly limited, but is preferably 20 cSt or more, more preferably 50 cSt or more, and is preferably 800 cSt or less, more preferably 600 cSt or less. The flash point (COC method) of the hydrocarbon rubber softener is preferably 200° C. or more, more preferably 250° C. or more.

[0047] The paraffinic rubber softener of component (D) can be obtained as a commercially available product. Examples of the commercially available product include Nippon Oil Polybutene (registered trademark) HV series manufactured by JX Nippon Oil & Energy Corporation and Diana Process Oil (registered trademark) PW series manufactured by Idemitsu Kosan Co., Ltd., and the like. The relevant product can be appropriately selected from these and used.

[0048] In the flame-retardant polyolefin resin composition of the present invention, the content of the softener of component (D) is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 8 parts by mass, even more preferably 1 to 6 parts by mass, and particularly preferably 2 to 6 parts by mass, per 100 parts by mass of the total of components (A).

[0049] By containing the softener of component (D) in the above range, the flame-retardant polyolefin resin composition of the present invention can obtain sufficient moldability and oil resistance due to component (D) while fully obtaining the blending effects of the other components.

[0050] <Other ingredients> The flame-retardant polyolefin resin composition of the present invention may contain various additives other than the above components (B) to (D) within the range that does not significantly impair the effects of the present invention.

[0051] Examples of additives include heat stabilizers, antioxidants, lubricants, and copper damage inhibitors. Examples of heat stabilizers and antioxidants include hindered phenols, phosphorus compounds, hindered amines, sulfur compounds, copper compounds, and alkali metal halides, and for example, the "Irganox" (registered trademark) series manufactured by BASF Japan can be used. Examples of lubricants include zinc stearate, and for example, "Zinc Stearate N" (registered trademark) manufactured by Tannan Chemical can be used. Examples of copper damage inhibitors include "Songnox 1024-PW" (registered trademark) manufactured by Songwon International Japan. These additives may be used alone or in any combination and ratio of two or more types.

[0052] When these additives are added, the total amount of these additives is usually 2 parts by mass or less, for example, in the range of 1 to 2 parts by mass, per 100 parts by mass of the total of components (A) to (D).

[0053] The flame-retardant polyolefin resin composition of the present invention may contain a thermoplastic resin or an elastomer other than the above component (A).

[0054] Examples of thermoplastic resins other than component (A) include polyphenylene ether resins, polyamide resins such as nylon 6 and nylon 66, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyoxymethylene resins such as polyoxymethylene homopolymers and polyoxymethylene copolymers, polymethyl methacrylate resins, and polyolefin resins (excluding those corresponding to component (A)). Examples of elastomers other than component (A) include styrene elastomers, polyester elastomers, and polybutadiene.

[0055] However, when the flame-retardant polyolefin resin composition of the present invention contains a thermoplastic resin or elastomer other than component (A) in order to more effectively obtain the effect of including component (A) as a resin component, the content thereof is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less, per 100 parts by mass of the total of components (A) to (D).

[0056] [Method for producing flame-retardant polyolefin resin composition] The flame-retardant polyolefin resin composition of the present invention is obtained by kneading the mixture of the present invention containing components (A) to (D) and other components used as necessary in predetermined amounts.

[0057] [Molded objects / Applications] The flame-retardant polyolefin resin composition of the present invention can be molded into a molded article by a molding method usually used for polyolefin resin compositions, for example, various molding methods such as injection molding, extrusion molding, blow molding, and compression molding. Among these, injection molding and extrusion molding are preferred. In addition, a molded article can be obtained by performing secondary processing such as lamination molding and thermoforming after these moldings. In particular, the flame-retardant polyolefin resin composition of the present invention has excellent extrusion moldability and reduces the generation of eye plugs and bumps during molding, so it is suitable for extrusion molding, especially profile extrusion molding.

[0058] From the viewpoint of durability, the molded article of the present invention preferably has a tensile strength of 10 to 17 MPa, more preferably 14 to 17 MPa, measured under the conditions of JIS K6723. Also, from the viewpoint of durability, the molded article of the present invention preferably has a tensile elongation of 600 to 900%, more preferably 700 to 900%, measured under the conditions of JIS K6723. EXAMPLES

[0059] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples as long as it does not exceed the gist of the invention. The values ​​of various production conditions and evaluation results in the following examples are meant as preferred upper or lower limit values ​​in the embodiment of the present invention, and the preferred range may be a range defined by a combination of the above-mentioned upper or lower limit values ​​and the values ​​of the following examples or values ​​of the examples.

[0060] [Raw materials] The raw materials used in the following Examples, Comparative Examples, and Reference Examples are as follows.

[0061] [Component (A): Ethylene-based resin component] A1: Novatec LL (registered trademark) UJ990 manufactured by Japan Polyethylene Corporation Linear low density polyethylene Density: 0.937g / cm 3 MFR (190℃, 21.2N load): 35g / 10 minutes A2: Engage (registered trademark) ENR7256 manufactured by Dow Chemical Company Ethylene-α-olefin copolymer Density: 0.885g / cm 3 MFR (190℃, 21.2N load): 2.5g / 10min A3: Evaflex (registered trademark) EV360 manufactured by Mitsui DuPont Polychemicals Ethylene-vinyl acetate copolymer Density: 0.95g / cm 3 MFR (190℃, 21.2N load): 2.0g / 10min A4: Modic (registered trademark) M122 manufactured by Mitsubishi Chemical Corporation Linear low density polyethylene Density: 0.92g / cm 3 MFR (190℃, 21.2N load): 1.3g / 10 minutes

[0062] [Component (B): flaky magnesium hydroxide] B1: Kisuma (registered trademark) 10A manufactured by Kyowa Chemical Industry Co., Ltd. Scaly magnesium hydroxide Average diameter: 4.0μm Average thickness: 60nm Aspect ratio: 70

[0063] [Component (b): Granular magnesium hydroxide] b1: Magseeds (registered trademark) S6 manufactured by Konoshima Chemical Co., Ltd. Granular Magnesium Hydroxide Average particle size: 1.0μm

[0064] [Component (C): Silicone] C1: Toray Dow Corning SH200 FLUID 12500 CS Polydimethylsiloxane Kinematic viscosity (25℃): 12500cSt C2: Evonik Tegomer V-Si4042 Organically Modified Siloxane

[0065] <Component (D): Softener> D1: Diana Process Oil (registered trademark) PW90 manufactured by Idemitsu Kosan Co., Ltd. Paraffin-based rubber softener Kinematic viscosity (40℃): 95.5cSt Flash point: 272℃

[0066] <Other ingredients> Sulfur-based antioxidant: Irganox (registered trademark) PS802FL, manufactured by BASF Japan Phenolic antioxidant: Irganox (registered trademark) IRGANOX 1010 manufactured by BASF Japan Lubricant: Zinc Stearate N (registered trademark) manufactured by Tannan Chemical Copper damage inhibitor: Songnox(R) 1024 PW manufactured by Songwon International Japan

[0067] [Evaluation method] The flame-retardant polyolefin resin compositions in the following Examples and Comparative Examples were evaluated as follows.

[0068] <Oxygen Index> The pellets were used to form a sheet having a thickness of 2 to 3 mm using an open roll with a surface temperature of 130° C., and then pressed to a thickness of 3 mm (temperature 190° C., pressure 10 MPa) to obtain a pressed sheet. The oxygen index of this 3 mm pressed sheet was measured in accordance with JIS K7201.

[0069] <Tensile strength / tensile elongation> The pellets were extruded at 180°C using a single screw extruder with a diameter of 20 mm to obtain an extruded tape with a width of 50 mm and a thickness of 1 mm. The tensile strength and tensile elongation of this 1 mm thick extruded tape were measured in accordance with JIS K6723. A No. 3 dumbbell was used as the test piece, and the tensile speed was 200 mm / min.

[0070] <Moldability> The obtained pellets were used in an extruder having a diameter of 20 mm, at a temperature of 180°C and a screw rotation speed of 60 rpm to produce an extruded tape having a thickness of 1 mm and a width of 4 cm. The extrusion load was evaluated.

[0071] <mfr> The MFR of the obtained pellets was measured under the conditions of a temperature of 190° C. and a load of 21.2 N in accordance with JIS K7210-1.

[0072] [Example 1] 30 parts by mass of (A1), 55 parts by mass of (A2), 10 parts by mass of (A3), 5 parts by mass of (A4), 5 parts by mass of (B1), 4 parts by mass of (C1), 5 parts by mass of (D1), 0.5 parts by mass of sulfur-based antioxidant, 0.5 parts by mass of phenol-based antioxidant, 0.5 parts by mass of lubricant, and 0.1 parts by mass of copper damage inhibitor were inserted into a pressure kneader with a capacity of 1.0 L, kneaded at a jacket setting temperature of 80 ° C. of the pressure kneader, and kneading was stopped when the resin temperature reached 180 ° C. due to self-heating caused by shear. The kneaded product obtained was further sheeted by an open roll with a surface temperature of 120 ° C., and then pelletized by a pelletizer to obtain pellets of a flame-retardant polyolefin-based resin composition.

[0073] [Examples 2 to 4, Comparative Examples 1 to 8, Reference Example 1] Pellets of a polyolefin resin composition were obtained in the same manner as in Example 1, except that the components (A) to (D) in the proportions shown in Table 1 were used, and 0.5 parts by mass of a sulfur-based antioxidant, 0.5 parts by mass of a phenol-based antioxidant, 0.5 parts by mass of a lubricant, and 0.1 parts by mass of a copper inhibitor were further added.

[0074] The above-mentioned oxygen index, tensile strength, tensile elongation, moldability, and MFR were measured and evaluated for the pellets of the polyolefin resin compositions obtained in Examples 1 to 4, Comparative Examples 1 to 8, and Reference Example 1. The results are shown in Table 1.

[0075] [Table 1]

[0076] [Evaluation Results] As shown in Table 1, the flame-retardant polyolefin resin compositions of Examples 1 to 4 have high oxygen indexes and excellent flame retardancy, and also have suitable MFRs and excellent moldability, as well as suitable extrusion loads and excellent molding processability. The results of Examples 1 to 4 show that increasing the flaky magnesium hydroxide component (B1) tends to increase the oxygen index, but on the other hand, the tensile strength and tensile elongation tend to decrease and the extrusion load tends to increase.

[0077] Comparative Example 1, which does not contain flaky magnesium hydroxide (B1), has good tensile strength, tensile elongation, moldability, and MFR, but has a low oxygen index of 18.5 and is poor in flame retardancy. In Comparative Example 2 and Comparative Example 4, scaly magnesium hydroxide (B1) and granular magnesium hydroxide (b1) are used, respectively, but there is no significant difference in the oxygen index, tensile strength, tensile elongation, and moldability. On the other hand, in Comparative Example 3, in which 4 parts by mass of silicone oil (C1) was added to Comparative Example 4 (oxygen index 20), the oxygen index was only slightly higher at 22.5, whereas in Example 2, in which 4 parts by mass of silicone oil (C1) was added to Comparative Example 2 (oxygen index 20.5), the oxygen index was 27.5, which shows that the oxygen index was significantly higher. Therefore, it can be seen that the combination of flaky magnesium hydroxide (B1) with silicone oil (C1) significantly improves the oxygen index compared to the combination with conventional magnesium hydroxide (b1).

[0078] The results of Comparative Examples 5 to 7 show that when the flaky magnesium hydroxide component (B1) is further increased to 100 parts by mass, the oxygen index increases to 28, but the MFR of the resin composition tends to decrease, the tensile properties tend to deteriorate, and the molding processability is also unfavorable. The results of Comparative Example 8 show that when the flaky magnesium hydroxide component (B1) was contained at 4 parts by mass, the oxygen index was 21, which resulted in poor flame retardancy. In Reference Example 1, the magnesium hydroxide (b1) was increased to 100 parts by mass compared to Comparative Example 3. Although the oxygen index increased to 26, the tensile strength and moldability were significantly decreased, making the product unsuitable for practical use. [Industrial Applicability]

[0079] The flame-retardant polyolefin resin composition of the present invention can be used in a wide range of fields, such as electric wires, electric wire covering materials, electric wire protection tubes, tubes, miscellaneous goods, etc. The flame-retardant polyolefin resin composition of the present invention is particularly suitable as an electric wire covering material among the above-mentioned.< / mfr>

Claims

1. A flame-retardant polyolefin-based resin composition comprising the following components (A) to (D), wherein the flame-retardant polyolefin-based resin composition contains 5 to 50 parts by mass of component (B) per 100 parts by mass of component (A). Component (A): An ethylene-based resin component using 30 to 40 mass% of linear low-density polyethylene, 50 to 60 mass% of an ethylene-α-olefin copolymer (excluding the linear low-density polyethylene), and 5 to 15 mass% of an ethylene-vinyl acetate copolymer in a total amount of 100 mass%. Component (B): Scaly magnesium hydroxide Component (C): Silicone oil Component (D): Hydrocarbon-based rubber softener

2. 2. The flame-retardant polyolefin resin composition according to claim 1, wherein the MFR (190° C., 21.2 N load) of the flame-retardant polyolefin resin composition is 1.0 to 5.0 g / 10 min.

3. 3. The flame-retardant polyolefin resin composition according to claim 1, comprising 7 to 50 parts by mass of said component (B) per 100 parts by mass of said component (A).

4. A molded article using the flame-retardant polyolefin resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Flame retardant resin composition

    JP2002146124A

  • Flame-retardant resin composition

    JP2002234970A

  • Oil-resisting flame-retardant resin composition

    JP2002284935A

  • Resin composition and insulated wire

    JP2005068388A

  • Flame-retardant polyolefin resin composition

    JP2006143896A